Reduction in Parasympathetic Tone During Sleep in Children With Habitual Snoring - Lopes, Maria-Cecilia; Spruyt, Karen; Azevedo-Soster, Leticia; Rosa, Agostinho; Guilleminault, Christian (Frontiers in Neuroscience, 2019)
Introduction: Changes in the autonomic nervous system due to Obstructive Sleep Apnea (OSA) during the life span have been described. Some pediatric studies have shown cardiovascular effects in children who do not fit the criteria for OSA; namely children with mild sleep disordered breathing. Objective: We investigated heart rate variability (HRV) during sleep in children with chronic snoring and flow limitation events during sleep. Methods: 10 children and adolescents with chronic snoring and an apnea hypopnea index < 1, associated to high Respiratory Index, and 10 controls matched for age, gender and Tanner stage were monitored following one night of habituation in the sleep laboratory. HRV was studied at each sleep stage. The time and frequency domains were calculated for each 5-minute period. Results: All patients were chronic heavy snorers. They presented an apnea hypopnea index= 0.8, respiratory disturbance index=10.2/h with lowest O2 saturation 96.1±2.4%. The total power of HRV was decreased in all stages (p < 0.05). There was also a decrease in NN50 and pNN50 during all sleep stages compared to healthy controls (p=0.0003 and p=0.03 respectively). Conclusion: A reduction in parasympathetic tone was found in the patients group. This may represent an autonomic impairment during sleep in children with mild SDB. A reduction in HRV in children with habitual snoring could be associated with possible increases in cardiovascular risk in adulthood. Significance: The study indicates that children with habitual snoring have important parasympathetic tone changes during sleep.